Pemasangan Stent pada Pasien dengan Myocardial Bridging Simtomatik - Johan Winata; Eben Reppi; Bambang Budiono; Reggy L Lefrandt (Jurnal Kardiologi Indonesia, 2013)
Background : Myocardial bridging is a congenital coronary anomaly withmostly benign course throughout life. However, several pathological clinicalmanifestations may accompany myocardial bridging, such as arrhythmia,angina, depressed left ventricular function, myocardial stunning, myocardialinfarction, and sudden death. Symptomatic management with anti anginalagents should be adequate in most cases. Stenting, surgical resection ofthe bridge (myotomy), and coronary bypass surgery are only reserved forthe rare patient with severe symptoms.Case Report : A 44 year old man was admitted to the hospital because ofthe recurrent episodes of palpitations, syncope and chest pain. ECG showedsinus rhythm with bigeminy ventricular extra systoles. Echocardiographyshowed no regional wall motion abnormalities with normal ejection fraction.Coronary angiography showed myocardial bridging in mid LAD withno associated atherosclerotic coronary disease.Recurrent episodes of angina and non-sustained VT were detected duringobservation in ICCU, despite anti-arrhytmic drug treatment and Kaliumcorrection. Decision was made to perform PCI to cover bridging segmentusing drug eluting stent (DES). Post stent angiography showed no subsequentmilking effect of systole with improvement in the occurrence ofarrhythmia. Holter monitoring which was done 1 week after PCI showedno ventricular extrasystole found. Clinical evaluation and treadmill test at3 months after the procedure demonstrated good clinical condition andthe patient remained free of symptoms.Conclusion : A successful coronary stenting to mid LAD due to myocardialbridging with persistent symptoms despite medial therapy. A thorough followup should be done to identify the possibility of luminal narrowing causedby intimal proliferation or stent fracture due to external compression.